Buddhism and Whiteness critical reflections - Yancy, George; McRae, Emily, 1981- (Philosophy of race., 2019)
"In this unprecedented book, contributors use Buddhist philosophical and contemplative traditions, both ancient and modern, and deploy critical philosophy of race, and critical whiteness studies, to address the proverbial elephant in the room-whiteness"--